Zeolite/Cellulose Acetate (ZCA) in Blend Fiber for Adsorption of Erythromycin Residue From Pharmaceutical Wastewater: Experimental and Theoretical Study - Jodeh, Shehdeh; Erman, Israa; Hamed, Othman; Massad, Younes; Hanbali, Ghadir; Samhan, Subhi; Dagdag, Omar; Kaya, Savaş; Serdaroğlu, Goncagül (Frontiers in Chemistry, 2021)
The expanding amount of remaining drug substances in wastewater adversely affects both the climate and human well-being. In the current investigation, we developed new cellulose acetic acid derivation/zeolite fiber as an effective technique to eliminate erythromycin (ERY) from wastewater. The number of interchangeable sites in the adsorbent structures and the ratio of ERY to the three adsorbents were identified as the main reasons for the reduction in adsorption as the initial ERY concentrations increased. Additionally, for all adsorbents, the pseudo–second-order modeling showed better fitting for the adsorption than the pseudo–first-order modeling. However, the findings obtained in the pseudo–first-order model were still enough for explaining the sorption kinetics of ERY, showing that the surface displayed all chemisorption and physi-sorption adsorption processes by both adsorbents. The R2 for the second order was very close to 1 for the three adsorbents in the case of pseudo–second-order. The adsorption capacity reached 17.76 mg/g. The three adsorbents showed negative values of ΔH, and these values were −6,200, −8,500, and −9600 kJ/mol for zeolite, CA, and ZCA, respectively, and this shows that the adsorption is exothermic. The desorption analysis shows no substantial loss of adsorption site after three trials, indicating higher stability and resilience of the three adsorbents, indicating a strong repeatability of their possible use in adsorption without contaminating the environment. In addition, the chemical attitude and possible donor–acceptor interactions of ERY were assessed by the quantum chemical parameters (QCPs) and NBO analysis performed, at the HF/6-311G** calculations.